Quality Evaluation of Several Brands of Bottled Mineral Water from Egypt and Saudi Arabia - Abd El Aal, S.A.; El-Saftawy, A.A.; Alkadi, M.; Salama, S.; Kandil, S. (Asian Journal of Chemistry, 2015)
Twenty four brands of uncarbonated ground bottled water in Egypt and Saudi Arabia markets were analyzed using different techniques for evaluating their quality. To identify and classify the major and minor elements concentrations of the studied water samples, inductively coupled plasma optical emission spectroscopy (ICP-OES) technique was used. The water quality is also judged by the percent of total dissolved salts, conductivity and pH. The natural radioactivity was considered as well. The quality of water brand was also determined by analyzing the used plastic bottle, Therefore in the present work, the chemistry of the water bottles was investigated using FTIR technique. The obtained results were compared to several international standards; International Bottled Water Association (IBWA), United States Food and Drug Administration (FDA) and United States Environmental Protection Agency (EPA). All elements were less than the limits of the three international standards, except arsenic in K4, K9 and E4 samples, lead appeared only in K1 and K8, selenium in K1 was more than the limit in International Bottled Water Association but less under United States Food and Drug Administration and United States Environmental Protection Agency.